Health Behaviors and Patients with Coronary Artery Disease (CAD) : Role of Self-efficacy - Chobarunsitti, Chayanis; Prakobchai, Sattha (Journal of Food Health and Bioenvironmental Science, 2023)
Cardiac disease is a major risk of mortality and morbidity globally. Patient with Coronary artery diseases are more likely than other chronic disease in poor health behavior either pre-treatment or post-treatment. Even though cardiac patients tried to seek the ways to promote their health, they might face with the difficulties to change the behavior. Numerous studies showed that self-efficacy plays a crucial role as a buffer to perform activity as reflect personal beliefs and confidence. We synthesize the evidences on self-efficacy and health behavior regarding smoking behavior, alcohol consumption, eating behavior, physical activity or exercise behavior and stress management.We found that most of the researchers successfully applied self-efficacy to promote physical activity or exercise among patients with coronary artery disease in short term period.Nurses should assess functional status and provide health education to promote well-being and encourage patients to perform and maintain their capability on health-promoting behaviors.